2011
DOI: 10.1111/j.1399-5448.2010.00660.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia, S-ACE and ACE genotypes in a Danish nationwide population of children and adolescents with type 1 diabetes

Abstract: This large nationwide cohort has identified an increased risk for hypoglycemia associated with higher S-ACE level, however only in girls. A strong association was found between ACE genotype and S-ACE levels, but ACE genotype was not related to risk of hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Most association studies were performed on small sample sizes, without adjusting for insulin dose requirement or other non‐genetic predictors of HbA1c level, and should therefore be interpreted with caution. These candidate gene association studies have never been or have been poorly replicated, except for angiotensin I converting enzyme (ACE) gene . Five of the 13 selected studies reported significant or suggestive associations, which were however never replicated …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most association studies were performed on small sample sizes, without adjusting for insulin dose requirement or other non‐genetic predictors of HbA1c level, and should therefore be interpreted with caution. These candidate gene association studies have never been or have been poorly replicated, except for angiotensin I converting enzyme (ACE) gene . Five of the 13 selected studies reported significant or suggestive associations, which were however never replicated …”
Section: Resultsmentioning
confidence: 99%
“…Three other loci were tested: (1) HLA‐DRB1 and ‐DQB1 haplotypes, conferring the highest risk for T1D; (2) the ACE, for its possible role in diabetic nephropathy and hypoglycaemia and (3) apolipoprotein E (APOE) . None of these genes was significantly associated with HbA1c in T1D patients.…”
Section: Resultsmentioning
confidence: 99%
“…This has consistently been shown in seven studies in five different cohorts by four independent research groups. [1][2][3][4][5][6][7] One study reported an additive effect of presence of three RAS components -high serum ACE activity, high plasma angiotensinogen concentration and homo-or heterozygosity for the A-allele of the X chromosome-located angiotensin-II receptor subtype 2 1675G/A polymorphism -on the risk of severe hypoglycaemia in type 1 diabetes. 8 This finding suggests that increased angiotensin II receptor subtype 1 activation that is not counterbalanced by subtype 2 activation is detrimental during hypoglycaemia in subjects with type 1 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…We previously speculated whether genetic factors are implicated and reported a high rate of severe hypoglycaemia in type 1 diabetic subjects carrying the common deletion-allele of the angiotensin-converting enzyme (ACE) gene that confers high enzyme activity in blood and tissues (9). This finding has been reproduced in six studies in five different populations by four independent research groups (10, 11, 12, 13, 14, 15). Schouwenberg and coworkers showed in healthy adults that possessing the Arg Arg (vs the Gly Gly) polymorphism of the β2-adrenergic receptor may to some extent protect against the development of hypoglycaemia unawareness (16, 17), a major risk indicator of severe hypoglycaemia.…”
Section: Introductionmentioning
confidence: 55%
“…The only hitherto consistently reported biomarkers of severe hypoglycaemia in type 1 diabetes are undetectable C-peptide levels (9, 4), low HbA1c (40, 41, 42) and high serum ACE activity (10, 11, 12, 13, 14, 15). However, these markers only explain a minor proportion of the risk variation between subjects.…”
Section: Discussionmentioning
confidence: 99%